Two decades of surveillance data show late presentation among a diverse group of women diagnosed with HIV in Victoria, Australia - Clarissa Moreira; Alison Boughey; Kathleen Elizabeth Ryan; Nasra Higgins; Jessica Rotty; Michael West; Margaret Hellard; Mark Stoové; Carol El‐Hayek (Elsevier, 2019)
Abstract Objective: To develop an HIV response suited to women and to inform appropriate services, we describe the characteristics of women diagnosed and living with HIV using 22 years of high‐quality surveillance data. Methods: Data on women newly diagnosed with HIV between 1994 and 2016 and women living with diagnosed HIV in Victoria at 31 December 2016 were extracted from the Victorian Public Health Surveillance System. Descriptive analysis by place of birth was performed and Poisson regression used to assess trends over time. Results: There were 465 new diagnoses among women in Victoria between 1994 and 2016 and 613 women living with HIV in 2016. Women were diagnosed late, and frequently reported no HIV testing history, AIDS‐defining illness or other symptoms of HIV at diagnosis. These indicators of delayed diagnosis were even greater for non‐Australian‐born women. Conclusions and implications for public health: For Victoria to reach the ambitious targets for diagnosis, treatment and viral suppression in 95% of people living with HIV, prevention programs and efforts to increase early diagnosis as well as support services must consider the epidemiology and diversity of women.